2013
DOI: 10.1021/ja405680p
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Platinum Catalysts on Nanowire Surfaces for Photoelectrochemical Water Reduction

Abstract: The photocathodic hydrogen evolution reaction (HER) from p-type Si nanowire (NW) arrays was evaluated using platinum deposited by atomic layer deposition (ALD) as a HER cocatalyst. ALD of Pt on the NW surface led to a highly conformal coating of nanoparticles with sizes ranging from 0.5 to 3 nm, allowing for precise control of the Pt loading in deep submonolayer quantities. The catalytic performance was measured using as little as 1 cycle of Pt ALD, which corresponded to a surface mass loading of ∼10 ng/cm(2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
218
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(238 citation statements)
references
References 39 publications
11
218
0
1
Order By: Relevance
“…Atomic layer deposition (ALD) is an established technique to deliver materials to high-aspect-ratio nanostructures in a conformal and ultrathin fashion (57)(58)(59). We conformally coated CFP with MoO 3 by ALD (Materials and Methods) (60), which was then converted to MoS 2 by the same rapid sulfurization process (the as-grown catalyst is donated as ALD MoS 2 ).…”
Section: Significancementioning
confidence: 99%
“…Atomic layer deposition (ALD) is an established technique to deliver materials to high-aspect-ratio nanostructures in a conformal and ultrathin fashion (57)(58)(59). We conformally coated CFP with MoO 3 by ALD (Materials and Methods) (60), which was then converted to MoS 2 by the same rapid sulfurization process (the as-grown catalyst is donated as ALD MoS 2 ).…”
Section: Significancementioning
confidence: 99%
“…[8][9][10][11] ALD has also been used to apply both conformal and nanoparticulate catalysts with low parasitic light absorption to nanostructured light absorbers. [12][13][14][15] The importance of ALD in the development of PEC devices is likely to continue to grow as nanostructuring appears to be a promising way to increase effi ciency in these devices. [ 16,17 ] One of the main effi ciency losses in the splitting of water occurs in the driving of the oxygen evolution reaction (OER).…”
Section: Doi: 101002/aenm201500412mentioning
confidence: 99%
“…To run overall solar water splitting in a full PEC device, both individual photocathode and photoanode should provide a low onset potential in one specific electrolyte in a way that their photocurrents cross each other [1]. There has been tremendous progress on individual photoelectrodes with high cathodic or anodic performances [2,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], however, coupling of most of such photoelectrodes to build a PEC tandem cell has been difficult due to some limitations such as operation of photoelectrodes in different electrolytes, high onset potentials that prevent the crossing of photocurrents, etc. Indeed, Mor et al have demonstrated metal oxide nanotube arrays for self-biased hydrogen generation cell, in which the correspondent photocathode and photoanode were immersed in 0.1 M Na 2 HPO 4 and 1 M KOH, respectively, achieving a photoconversion efficiency of 0.30% [25].…”
Section: Introductionmentioning
confidence: 99%